Rethinking Indonesian Constitutional Amendments: The Prospects and Perils of Judicial Review - Nggilu, Novendri M.; Perwira, Indra; Abdurahman, Ali; Moha, Mohamad Rivaldi; Rachmaniar, Adelia (Journal of Indonesian Legal Studies, 2024)
This article aims to evaluate the constitutional design of Indonesia's regulatory review system, which is administered by two institutions with judicial power. It also looks into the various obstacles that will arise when judicial review of constitutional amendments is put into practice in Indonesia. Statutory approaches are used in this article. The outcome demonstrates that the Indonesian constitution contains unchangeable provisions and that there is experience with both formal and informal, unusual constitutional amendments. These factors require the establishment of a judicial review mechanism to supervise constitutional amendments carried out in accordance with custom and as stipulated in the constitution, as well as to maintain and preserve the basic identity and structure of the constitution in order to prevent pragmatic constitutional amendments from damaging, eliminating, or undermining it. Challenges that the Constitutional Court will confront in its role as a judicial implementing actor in reviewing constitutional amendments when they are implemented in Indonesia in the future include resistance that will arise from the People's Consultative Assembly, intervention, and intimidation by other branches of power towards the Constitutional Court, as well as defiance of the decisions of the Constitutional Court, especially regarding the unconstitutionality of constitutional amendments.